2003
DOI: 10.2114/jpa.22.159
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Depression, Lifestyle and Quality of Life in the Community Dwelling Elderly: A Comparison between Gender and Age Groups

Abstract: This study aimed to comprehensively investigate the comprehensive relationships between depression and the characteristics of lifestyle and quality of life (QOL) of healthy, community dwelling elderly, and compare them according to gender and age groups. 1302 subjects (657 males and 645 females) were used for analysis. The investigators in this study were researchers working at universities in each prefecture. Data collection was conducted in a general delivery survey and interview setting or an education clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
62
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 14 publications
10
62
2
1
Order By: Relevance
“…Ramos and Wilmoth [23] reported that older people living alone had two times more depressive symptoms than the ones living with spouse. As in many other studies, the prevalence of depressive symptoms in older adults living alone was significantly higher than others [24].…”
Section: Discussionsupporting
confidence: 73%
“…Ramos and Wilmoth [23] reported that older people living alone had two times more depressive symptoms than the ones living with spouse. As in many other studies, the prevalence of depressive symptoms in older adults living alone was significantly higher than others [24].…”
Section: Discussionsupporting
confidence: 73%
“…QoL may also serve as a prognostic measure and predictor for such other outcomes as survival (2-5). Chronic illnesses are often associated with poor QoL (6). Patients undergoing chronic dialysis treatment have a poorer QoL compared with the general population (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the elderly have most likely experienced life events that negatively affect their mental health, such as retirement, loss of economic and social infrastructure, and bereavement for a deceased spouse, family members and close friends (3)(4)(5). Because the deterioration of mental health is considered to negatively affect activities in daily life and physical condition, the assessment and maintenance of mental health are considered to be important, particularly in the case of the elderly (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%